Philosophy-Based Da'wah in Digital Media in the Perspective of Discourse on Studying Philosophy Fahruddin Faiz on YouTube MJS Channel - Arinil Haq (ASTEEC, 2025)
This study aims to analyze the construction of da'wah discourse in the